2020
DOI: 10.1039/d0nr03305g
|View full text |Cite
|
Sign up to set email alerts
|

Water deteriorates lubricating oils: removal of water in lubricating oils using a robust superhydrophobic membrane

Abstract: Lubricating oil failure caused by water is solved by a robust membrane that shows steady performance in regard to extreme water repellency, high-efficiency purification of lubricating oils, and low wear volume even after harsh mechanical damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…This may be due to the precipitation of PVA winding on the GO sheets (see Figure 4F). For the XRD spectrum of FGPA, there was an extra small peak at 15.8°, which was due to the embedded fluorine functional group 56 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the precipitation of PVA winding on the GO sheets (see Figure 4F). For the XRD spectrum of FGPA, there was an extra small peak at 15.8°, which was due to the embedded fluorine functional group 56 …”
Section: Resultsmentioning
confidence: 99%
“…For the XRD spectrum of FGPA, there was an extra small peak at 15.8 , which was due to the embedded fluorine functional group. 56 XPS spectra can be used to characterize the elemental content, composition, and chemical bond in GO, GPA, and FGPA, and reflect the reaction process through the change in spectra. In the XPS fullrange spectra (see Figure S2), C peaks at 285 eV and O peaks at 532 eV were found in GO, GPA, and FGPA samples.…”
Section: Instruments and Characterizationmentioning
confidence: 99%
“…Superwetting control emerged as a popular topic in fundamental interface science field and can directly affect specific effects on solid surface in certain environment media, and would provide a powerful toolbox to solve complex and challenging problems in academic and industrial fields, [ 1–7 ] for example, efficiency and selectivity in catalysis process, [ 8,9 ] controllability in printing and patterning, [ 10,11 ] and sensitivity in surface analysis. [ 12,13 ] Although considerable attempts have recently been made to design and construct multifunctional superwetting surfaces, [ 4,14–20 ] especially for superantiwetting surfaces, [ 21–26 ] the defined superantiwetting states can only perform in single certain environment media, causing most of the significant interfacial applications to not be achieved in different media.…”
Section: Methodsmentioning
confidence: 99%
“…Superwetting control emerged as a popular topic in fundamental interface science field and can directly affect specific effects on solid surface in certain environment media, and would provide a powerful toolbox to solve complex and challenging problems in academic and industrial fields, [1][2][3][4][5][6][7] for example, efficiency and selectivity in catalysis process, [8,9] controllability in printing and patterning, [10,11] and sensitivity in surface analysis. [12,13] Although enables the challenging in-air superhydrophilic (IASHL) and IASOB states possible (Scheme 1B).…”
mentioning
confidence: 99%
“…In recent years, it has been considered as a new and effective way to construct Superhydrophobic Surfaces (SHSs) on Al and its alloys for prevent corrosion [6,7]. In addition, SHSs has attracted much attention in the fields of oil-water separation [8,9], anti-icing [10][11][12], self-cleaning [13,14] and drag reduction [15] due to its excellent hydrophobic performance (contact angle greater than 150°). However, reports have shown that the instability of the hydrophobic layer and the finiteness of the micro-nano structure led to the insufficient robustness of SHSs, which makes them easy to be destroyed under dynamic action and mechanical damage [16,17].…”
Section: Introductionmentioning
confidence: 99%